A Semiotic Analysis of Mental Health: Depression Reflected in Voices in My Head by Falling in Reverse Music Video - Ksatria, Aldo; Heriyati, Nungki (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This research discusses the meaning of mental health, specifically depression that is reflected in the lyrics and music video of the song titled Voices in My Head by Falling in Reverse. This research applied qualitative descriptive method along with Roland Barthes semiotic perspective to find the signification process in the data that is related to the issue, and also types of mental disorder limited to depression as outlined by Keliat. The findings reveal how both the lyrics and visual elements in the music video contribute to the representation of mental health issue, it also shows the common struggle of battling inner thoughts and refusing to seek help due to the fear of being shamed by the public. From the result, it can be concluded that the music video is helpful in portraying taboo subject of mental health issue, especially depression. Keywords: Semiotics, Music Video, Mental Health